Grain boundary segregation in immiscible nanocrystalline alloys. (March 2017) - Abdeljawad, Fadi; Lu, Ping; Argibay, Nicolas; Clark, Blythe G.; Boyce, Brad L.; Foiles, Stephen M.
Abstract: Grain boundary (GB) solute segregation has been proposed as a route to mitigate grain growth in nanocrystalline (NC) metals and stabilize their grain structures. An interesting effect emerges in immiscible NC alloys due to the intertwined roles of GB segregation and bulk alloy phase separation. Based on a diffuse interface model, we examine grain growth dynamics in immiscible NC alloys, where both GB solute segregation and bulk phase separation act in conjunction. Analytical treatments identify regimes, where the reduction in GB energy due to segregation is significant. Simulation results reveal that microstructural evolution and enhanced stability are a manifestation of the competing effects of GB heat of segregation and that of bulk heat of mixing. More specifically, in systems with low GB segregation precipitation of solute-rich domains and associated GB (Zener) pinning effects lead to sluggish grain growth rates. In contrast, GB solute segregation plays a more dominant role as the heat of segregation increases in comparison with the bulk heat of mixing. On the whole, this modeling framework provides an avenue to explore the role of bulk alloy and interfacial effects on the microstructural evolution of NC metals. Graphical abstract: Image 1